Electric mobility could help clean the air and boost green jobs as part of the COVID-19 recovery in Latin America and the Caribbean (2020)
The transition to electric mobility could help Latin America and Caribbean countries to reduce emissions and fulfill their commitments under the Paris Agreement on climate change, while generating green jobs as part of their recovery plans from the COVID-19 crisis, according to a new study.